2022
DOI: 10.3389/fpsyt.2022.768134
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relationships Between Abdominal Pain, Psychological Distress and Coping in Patients With IBS – A Time Series Approach

Abstract: ObjectiveIrritable bowel syndrome (IBS) is a chronic disease leading to abdominal pain that is often related to psychological distress. The aim of the study was to investigate the temporal relationships between abdominal pain and psychological variables in patients with IBS.MethodsThis longitudinal diary study included eight patients from a waiting group, recruited in the frame of a pilot intervention study. During their waiting time of 3 months the patients answered questions daily regarding somatic and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, a recent retrospective biobank cohort study (N = 65, 421) revealed that individuals living with both endometriosis and IBS are more likely to suffer from multiple co-occurring conditions and experience greater abdominal and pelvic pain compared to individuals with endometriosis or IBS alone [57]. In endometriosis and IBS, disease-related pain is signi cantly associated with increased symptoms of depression and anxiety, pain catastrophising and fatigue [35,37,40,[71][72][73], whilst disease severity may directly in uence how individuals with IBS adaptively cope with and respond to pain [74][75][76]. Accordingly, the presence of comorbid IBS-type symptoms in endometriosis potentially in uences individual responses to condition-related factors and may exacerbate adverse health outcomes, impairing overall HRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent retrospective biobank cohort study (N = 65, 421) revealed that individuals living with both endometriosis and IBS are more likely to suffer from multiple co-occurring conditions and experience greater abdominal and pelvic pain compared to individuals with endometriosis or IBS alone [57]. In endometriosis and IBS, disease-related pain is signi cantly associated with increased symptoms of depression and anxiety, pain catastrophising and fatigue [35,37,40,[71][72][73], whilst disease severity may directly in uence how individuals with IBS adaptively cope with and respond to pain [74][75][76]. Accordingly, the presence of comorbid IBS-type symptoms in endometriosis potentially in uences individual responses to condition-related factors and may exacerbate adverse health outcomes, impairing overall HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, trends for individuals with Endo+IBS were not stable, and after an initial decline in levels of pain catastrophising, results rebounded or diminished over time. These ndings suggest that the added burden of comorbid IBS-type symptoms may heighten catastrophic thinking about pain, or potentially increase individual sensitivity to cyclical changes or external and environmental stressors[71,84,85]. Given that health outcomes are directly affected by how individuals cope with and respond to pain, the development of personalised targeted interventions to address and support cognitive and emotional processes associated with pain catastrophising may help to optimise treatment success and improve overall QoL, for both individuals living with EndoOnly and individuals with Endo+IBS[79,85].…”
mentioning
confidence: 93%
“…Several mechanisms might explain this association. First, the association between digestives and suicide might reflect the increased prevalence of other health conditions among patients with psychiatric problems, including abdominal pain (e.g., Lexne et al [95]) and irritable bowel syndrome [56]. Similarly, psychiatric patients are more prone to poor lifestyle habits, increasing the likelihood of digestive problems in this group [84,124,137,151].…”
Section: Discussionmentioning
confidence: 99%